Prevalence of HIV/hepatitis B and HIV/hepatitis C coinfection among people of East, South, Central and West African ancestry in the United Kingdom. (1st August 2021) - Hung, Rachel; Patel, Nisha; Fox, Julie; Cosgrove, Catherine; Pett, Sarah L.; Burns, Fiona; Ustianowski, Andrew; Rosenvinge, Melanie; Bhagani, Sanjay; Dusheiko, Geoff; Childs, Kate; Post, Frank A.
Abstract : N/A: Regional variability in the prevalence of hepatitis B (HBV) and C (HCV) is reported in sub-Saharan Africa, although data for people with HIV are sparse. We determined the prevalence of HBV/HCV in 2473 people of African ancestry with HIV in the UK. Overall, 6.2% were co-infected with HBV and 1.3% with HCV. Central [adjusted odds ratio (aOR) 2.40 (95% confidence interval (CI) 1.23–4.67) and West [2.10 (1.29–3.41)] African ancestry was associated with HBV and Central [6.98 (2.00–24.43)] African ancestry with HCV. Abstract : Supplemental Digital Content is available in the text